PERANCANGAN SISTEM INFORMASI AKUNTANSI PENGELUARAN KAS ATAS BIAYA PERJALANAN DINAS DI SENTRA WYATA GUNA BANDUNG - Yogi Adha Nugraha; Muhammad Rizal Alfandhani; Ratnanto Aditiarno; Candra Mecca Sufyana (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2023)
A technical implementation unit of the Ministry of Social Affairs' Directorate General for Social Rehabilitation, Sentra Wyata Guna Bandung is involved in the social sector, which includes disaster response and other humanitarian efforts in various parts of Indonesia. A cash disbursement system is one of Sentra Wyata Guna Bandung's accounting methods. Where in this company's cash disbursement system does it meet the head office's operational requirements? The activities of officers on business trips or assignments as duty obligations at the Wyata Guna Sentra take place outside of the area where work operations are carried out. It is possible to say that business travel activities occur quite frequently, which results in frequent cash transfers for business travel expenses. One fact emerged from the study's findings: the manual nature of the cash disbursement report processing meant that official travel cash disbursement reports were susceptible to loss and error. calculation: the goal of this research for the final project is to learn about the use of a cash disbursement accounting system for official travel expenses and to learn about reports of cash disbursements on web-based computerized business trips.